Search for new naturally occurring strains of Pleurotus to improve yields. Pleurotus albidus as a novel proposed species for mushroom production - Lechner, Bernardo Ernesto (2011)
Background: The species of genus Pleurotus are worldwide cultivated. Aims: To evaluate growth, yield production and morphological variations of fruiting bodies obtained from the cultivation of fourteen naturally occurring Pleurotus strains isolated from Argentina. Methods: The strains growth was tested at different temperatures on Nobles’ medium. Substrates assayed were: supplemented Salix sawdust, supplemented and non supplemented wheat straw. The species studied were Pleurotus albidus, Pleurotus cystidiosus, Pleurotus djamor, Pleurotus ostreatus and Pleurotus pulmonarius. Results: The maximum rate growth was reached by strains of P. pulmonarius, P. albidus, and P. ostreatus. No relationship was found when optimal mycelium growth, incubation time and yields were compared. The highest yield was obtained with P. albidus on wheat straw (biological efficiency 171.3%) which overcame in 82% the yield obtained for the commercial strain in the same substrate. When morphological variations were analyzed for each species, significant differences were found among strains. It was also possible to find a naturally occurring strain of P. ostreatus with better biological efficiency than the commercial strain assayed. Conclusions: We propose the study of naturally occurring strains as a useful practice to improve yields of species of Pleurotus. Due to the high biological efficiency obtained we propose P. albidus as a new species for commercial production.